The Role of Islamic Education Teachers in Instilling Islamic Character Values among Junior High School Students in the Digital Era - Alsha Silvia Grymitha; Romlah Romlah; Fitriani Fitriani (Universitas Islam Negeri Fatmawati Sukarno Bengkulu, 2026)
ENGLISH: The Role of Islamic Education Teachers in Instilling Islamic Character Values among Junior High School Students in the Digital Era.Objective: This study aims to analyse the role of Islamic education teachers in instilling Islamic character values among students in the digital era at SMP Negeri 22 Bandar Lampung. Method: This study employed a descriptive qualitative approach, with data collected through observations, interviews, and documentation, using source and method triangulation. Results: The findings indicate that Islamic education teachers play roles as educators, mentors, role models, and evaluators through IMTAQ programs, ROHIS activities, and the integration of digital media in learning. The challenges encountered include excessive use of digital technology, declining discipline, and the influence of external social environments. The strategies implemented include role modelling, religious habituation, digital-based learning, and communication between schools and families. Conclusion: This study concludes that instilling Islamic character values in the digital era can be effectively implemented through structured religious programs and the educational use of digital technology. Contribution: This study contributes to the development of a digital-integrated Islamic character education model grounded in religious habituation, which may serve as a reference for Islamic educational institutions.INDONESIAN: Peran Guru Pendidikan Agama Islam Dalam Menanamkan Nilai-Nilai Karakter Islami Siswa SMP di Era DigitalTujuan: Penelitian ini bertujuan untuk menganalisis peran guru Pendidikan Agama Islam (PAI) dalam menanamkan nilai-nilai karakter Islami pada peserta didik di era digital di SMP Negeri 22 Bandar Lampung. Metode: Penelitian menggunakan pendekatan kualitatif deskriptif, pengumpulan data melalui observasi, wawancara, dan dokumentasi dengan teknik triangulasi sumber dan metode. Hasil: Temuan studi menunjukkan bahwa Guru PAI berperan sebagai pendidik, pembimbing, teladan, dan evaluator melalui program IMTAQ, kegiatan ROHIS, serta pemanfaatan media digital dalam pembelajaran. Tantangan yang dihadapi meliputi tingginya penggunaan teknologi digital, menurunnya kedisiplinan, dan pengaruh lingkungan luar sekolah. Strategi yang diterapkan meliputi keteladanan, pembiasaan religius, pembelajaran berbasis digital, serta komunikasi antara sekolah dan keluarga. Kesimpulan: Studi ini menyimpulkan bahwa penanaman nilai-nilai karakter Islami di era digital dapat berjalan efektif apabila didukung program religius yang terstruktur dan pemanfaatan teknologi digital secara edukatif. Kontribusi: Penelitian ini memberikan kontribusi dalam pengembangan model pendidikan karakter Islami berbasis pembiasaan religius terintegrasi digital yang dapat menjadi rujukan bagi institusi Pendidikan Islam.